1992
DOI: 10.1161/01.res.70.6.1081
|View full text |Cite
|
Sign up to set email alerts
|

Novel diazinone derivatives separate myofilament Ca2+ sensitization and phosphodiesterase III inhibitory effects in guinea pig myocardium.

Abstract: The inotropic state of the myocardium can be enhanced via an increase in cell Ca2+ loading or in myofilament responsiveness to Ca2+. Although different pharmacological agents combine these properties, no presently available drug acts predominantly as a myofilament sensitizer in situ. We have investigated the effects and the mechanism of action of novel diazinone derivatives, EMD 54622, EMD 53998, and EMD 54650 (developed by E. Merck, Darmstadt), on guinea pig myocardial preparations. Force- and ATPase-pCa rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…This is characterized by an increase in the apparent Ca 2+ sensitivity, as demonstrated by a decrease in the pCa 50 value, a decrease in the steepness of the pCa-tension relation, and an increase in maximum Ca 2+ -activated force. In addition, the positive inotropic effect of EGIS-9377 was associated with an increase in the relaxation time of isometric contraction, probably as a consequence of an increase in the duration of attachment of myosin cross-bridges, as reported for those of other Ca 2+ sensitizers (Lee and Allen 1991;Ventura et al 1992). The molecular mechanisms underlying the effect of EGIS-9377 at the level of the regulatory proteins which are responsible for these characteristics are as yet unknown and cannot be derived directly from the present results.…”
Section: Discussionsupporting
confidence: 61%
“…This is characterized by an increase in the apparent Ca 2+ sensitivity, as demonstrated by a decrease in the pCa 50 value, a decrease in the steepness of the pCa-tension relation, and an increase in maximum Ca 2+ -activated force. In addition, the positive inotropic effect of EGIS-9377 was associated with an increase in the relaxation time of isometric contraction, probably as a consequence of an increase in the duration of attachment of myosin cross-bridges, as reported for those of other Ca 2+ sensitizers (Lee and Allen 1991;Ventura et al 1992). The molecular mechanisms underlying the effect of EGIS-9377 at the level of the regulatory proteins which are responsible for these characteristics are as yet unknown and cannot be derived directly from the present results.…”
Section: Discussionsupporting
confidence: 61%
“…'11,216-221) EMD 53998 has both a Ca 21 sensitizing action and a PDE III-inhibitory action ,21S) and it has been shown that the former action is due to the (+) enantiomer (EMD 57033) and the latter to the (-) enantiomer (EMD 57439) (Table II).111,219,221) In skinned cardiac muscle fibers, the pCa-tension relationship was shifted to the left and maximal tension was increased in the presence of EMD 53998. 215,217,218) In intact myocardial cells, contractile force or shortening was increased without or with only a small increase 11,220,221) or with a decrease 216) in the amplitude of Ca 21 transients. The small increase in peak Ca 21 transients was due mainly to inhibition of PDE III and the subsequent accumulation of cyclic AMP indeed by the (-) enantiomer BM 57439.18,220,22') Neither the (+) enantiomer EMD 57033 nor the (-) enantiomer EMD 57439 affected binding of Ca 2+ ions to troponin C in skinned fibers of canine heart.")…”
Section: Frank-starling Mechanismmentioning
confidence: 99%
“…EMD 57439, a pure PDE III inhibitor) and (+) EMD 53998 (i.e. EMD 57033), a Ca 2+ sensitiser with minimal PDE III inhibitory actions in vitro (Ventura et al, 1992;Lues et al, 1993). Data on the cardiovascular actions of EMD 57033 in vivo are lacking.…”
Section: Introductionmentioning
confidence: 99%